Pulmonary Mycobacterium kansasii Infection Mimicking Malignancy on the 18F-FDG PET Scan in a Patient Receiving Etanercept: A Case Report and Literature Review. (20th October 2014) - Min, Zaw; Amlani, Mohan
Abstract : A 66-year-old male presented with chest pain, malaise, generalized weakness, and weight loss. He had been receiving etanercept injection for rheumatoid arthritis. Chest X-ray revealed a right upper lobe mass. Chest computed tomography (CT) showed a right apical mass, highly suggestive of a Pancoast tumor. The thoracic fluorine-18 fluoro-deoxy-glucose ( 18 F-FDG) positron emission tomography (PET) scan demonstrated significantly high metabolic pulmonary lesions with the standardized uptake value (SUV) of 12.5, consistent with lung cancer. The patient underwent bronchoscopy and bronchoalveolar lavage (BAL). BAL cytology was negative for malignant cells. BAL acid fast bacilli (AFB) smears were positive, and Mycobacterium kansasii was eventually isolated. He received a 12-month course of rifampin, isoniazid, and ethambutol. Interval resolution of pulmonary lesions was noted on follow-up serial CT chest studies. There has been increasing incidence of nontuberculous mycobacterial infections reported in patients treated with the antitumor necrosis factor-alpha (anti-TNF-alpha) agents. Infectious foci have an increased glucose metabolism which potentially causes a high FDG uptake on the 18 F-FDG PET scan, leading to undue anxiety and cost to the patients. This is the first reported case of pulmonary M. kansasii infection with a positive thoracic 18 F-FDG PET study mimicking malignancy in a patient on etanercept.